2019
DOI: 10.1371/journal.pone.0224936
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of small molecules into DNA in chromatin is primarily controlled by superhelical constraint

Abstract: The restricted access of regulatory factors to their binding sites on DNA wrapped around the nucleosomes is generally interpreted in terms of molecular shielding exerted by nucleosomal structure and internucleosomal interactions. Binding of proteins to DNA often includes intercalation of hydrophobic amino acids into the DNA. To assess the role of constrained superhelicity in limiting these interactions, we studied the binding of small molecule intercalators to chromatin in close to native conditions by laser s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…These architectural differences are reflected in global effects of functional consequences, as shown below. As compared to DKO H2A.Z nuclei, those of the DKO H2A.ZΔC line stained much more readily with intercalator dyes used at such low concentrations where dye binding is DNA topology dependent (54), and were much more readily digested using MNase, nickase and DNAse I (Fig. 3), suggesting major H2A.Z C-terminal tail-dependent overall differences in chromatin structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These architectural differences are reflected in global effects of functional consequences, as shown below. As compared to DKO H2A.Z nuclei, those of the DKO H2A.ZΔC line stained much more readily with intercalator dyes used at such low concentrations where dye binding is DNA topology dependent (54), and were much more readily digested using MNase, nickase and DNAse I (Fig. 3), suggesting major H2A.Z C-terminal tail-dependent overall differences in chromatin structure.…”
Section: Resultsmentioning
confidence: 99%
“…The large difference between the staining of the DKO H2A.Z and H2A.ZΔC nuclei with the two intercalating dyes would be unexpected if the dyes were applied at the usual concentration allowing for stoichiometric binding to the DNA. However, they were added at a lower concentration where their binding to the DNA is highly sensitive to the constrtained nucleosomal and to the plectonemic internucleosomal superhelicity (54). The H2A.ZΔC levels expressed in the nuclei of these DKO DT40 cells are about half of the H2A.Z levels in the same DKO background, but the total number of H3K9me3, H3K27me3, H2B nucleosomes and also the amount of DNA in the nuclei of the two cell types are similar (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Lipophilicity (LogP o/w) values of all synthesized compounds were in the range from 1.83 to 3.44 for mono-substituted compounds, and 3.10 to 6.31 for disubstituted compounds while their molecular weights are generally within the accepted range-with a few exceptions. The compounds were found with optimum number of hydrogen bonding donors (0-4) and hydrogen bonding acceptors (1)(2)(3)(4)(5)(6)(7)(8). The achieved results indicate that most of the compounds follow Lipinski rule and have a good partition coefficient.…”
Section: Admet Propertiesmentioning
confidence: 95%
“…In previous experiments, we demonstrated a number of nanoscale disturbances of dsDNA properties caused by anthracycline antibiotics. It has been suggested that the superhelical twist and higher order structures can prevent the DNA intercalation, and thus can serve as a natural barrier against some molecules [29]. It is always the question if and how these effects could have been observed in nanoscale, very often in an isolated experimental setup, and whether they reflect microscale properties of DNA.…”
Section: Biophysical Changes Are Reflected By Changes Of Nuclei Size mentioning
confidence: 99%